Sosialisasi dan Pelatihan Penggunaan QRIS sebagai Media Pembayaran Elektronik bagi Siswa SMK Wirorotomo Purwokerto - Yuniati, Trihastuti; Riano, Putra Pratama Okta; Samudra, Muhammad (Edumedia Solution, 2023)
The use of cash in payment transactions has several drawbacks, including time inefficiencies, unavailability of denominations for change, the risk of counterfeit money, and the risk of theft or robbery. This weakness can be overcome by having a digital payment system, one of which is Quick Response Code Indonesian Standard or known as QRIS technology. The students of SMK Wirorotomo Purwokerto as young generations with great potential in conducting financial transactions in the future, need to be given socialization regarding payment transactions using QRIS. With this socialization and training activity, it is hoped that it can support the government's policy direction to go digital and implement cashless payments.